Zdravotní pojištění
Zákon č. 592/1992 Zb. o poistnom na všeobecné zdravotné poistenie, v znení zákonov č. 10/1993 Zb., č. 15/1993 Zb., č. 161/1993 Zb., č. 324/1993 Zb., č. 42/1994 Zb. a č. 241/1994 Zb. Úplné znenie.